CIM17MMT04: A new maize hybrid with high yield potential released in Mexico. - CGIAR Research Program on Maize (2019)
The MasAgro seed companies have been adopting the hybrids released by the project (more than 30 hybrids have been released) and produced on a large scale. In 2019, they sold more than 20 CIMMYT hybrids, one of those hybrids was sold (adopted) for the first time in the Mexican market.